Thermal, spectral, and surface properties of LED light-polymerized bulk fill resin composites - YILMAZ ATALI, PINAR (WALTER DE GRUYTER GMBH, 2015)
The aim of this study was to evaluate the thermal, spectral, and surface properties of four different bulk fill materials - SureFil SDR (SDR, Dentsplay DETREY), QuixFil (QF, Dentsplay DETREY), X-tra base (XB, Voco) X-tra fil (XF, Voco) - polymerized by light-emitting diode (LED). Resin matrix, filler type, size and amount, and photoinitiator types influence the degree of conversion. LED-cured bulk fill composites achieved sufficient polymerization. Scanning electron microscope (SEM) analysis revealed different patterns of surface roughness, depending on the composite material. Bulk fill materials showed surface characteristics similar to those of nanohybrid composites. Based on the thermal analysis results, glass transition (T-g) and initial degradation (T-i) temperatures changed depending on the bulk fill resin composites.
Keywords: atomic force microscope; bulk fill composites; degree of cure; EMITTING DIODES LEDS; MECHANICAL-PROPERTIES; IN-VITRO; DENTAL COMPOSITES; MARGINAL ADAPTATION; CURE; CONVERSION; CAVITIES; DEPTH; RESTORATION